5 Relationships between infarct zone extracellular volume and clinical measures of ischaemia and reperfusion in acute STEMI survivors. (26th April 2015) - Carberry, J; Carrick, D; Haig, C; Rauhalammi, SM; Ahmed, N; Mordi, I; McEntegart, M; Petrie, M; Eteiba, H; Hood, S; Watkins, S; Lindsay, M; et al.
Abstract : Background: The clinical significance of infarct extracellular volume (ECV) post-STEMI is unknown. ECV can be estimated by cardiac magnetic resonance imaging (CMR) using T1 MOLLI maps. We measured infarct ECV in STEMI survivors, and assessed the relationships between ECV and markers of MI severity. Methods: STEMI survivors were enrolled in a single-centre cohort study (BHF MR-MI study – NCT02072850 ). Culprit artery flow was described by thrombus in myocardial infarction (TIMI) classification. CMR was performed at 1.5 Tesla (Siemens MAGNETOM Avanto) 2-days and 6-months post-MI, including T1-mapping with MOLLI before and 15-minutes after contrast (0.15 mmol/kg gadoterate meglumine). ECV was analysed by outlining regions-of-interest (ROIs) in infarcted myocardium, including microvascular obstruction, and left ventricular (LV) blood pool. ECV was calculated as the relaxation rate (R1=1/T1) for myocardium and LV blood pool before vs. after contrast, corrected for haematocrit. ECV was compared with TIMI-flow pre- and post-percutaneous coronary intervention (PCI) and ST-segment resolution. A reduction in ST-segment voltage of ≥70% was considered complete ST-resolution and <70% was considered incomplete ST-resolution. Results: 201 STEMI patients (age 58 ± 11 years; 156 (77%) male) were enrolled. Infarct ECV was similar at baseline and follow-up (51.3 ± 9.5% vs. 50.3 ± 12.0%, p = 0.1). Pre-PCI, 131 (65%) patients had TIMI-flow 0 and 70 (35%) had TIMI-flow 1–3. Post-PCI, 3 (1.5%) patients had TIMI-flow 0 and 198 (98.5%) had TIMI-flow 2–3. TIMI-flow 0 pre-PCI was associated with higher infarct ECV at baseline (p < 0.001) and follow-up (p = 0.004). TIMI-flow post-PCI was not associated with infarct ECV. ST-resolution was complete in 104 (52%) patients and incomplete in 96 (48%) patients. Incomplete ST-resolution was associated with higher infarct ECV at baseline (p = 0.001) and follow-up (p = 0.026) (Table 1 ). Conclusion: Preserved culprit artery flow and complete ST-resolution are associated with lower infarct ECV at baseline and follow-up. Clinical and electrocardiographic markers of MI severity are predictors of interstitial expansion in the infarct zone in STEMI patients.